BOUNDED SOLVABILITY OF MIXED-TYPE FUNCTIONAL DIFFERENTIAL OPERATIONS FOR FIRST ORDER - (:unkn) unknown (TEXAS STATE UNIV, 2016)
In this article, we study all boundedly solvable extensions generated by linear mixed-type (forward-backward) functional differential-operator expressions of first order in the Hilbert space of vector-functions on a finite interval. Our main tools are methods of operator theory. Also we study the structure of the spectrum of these extensions.
Keywords: Mixed-type functional differential expression; bounded solvable operator; spectrum